Effectiveness Of Geogebra Assisted â€œ5Eâ€ Learning Cycle On Studentsâ€™ Conceptual Understanding - Putri, Ni Nyoman Wulan Darma (Universitas Pendidikan Ganesha, 2021)
This study aimed to investigate the effectiveness of GeoGebra-assisted 5E Learning Cycle model toward student’s understanding of mathematical concept with control of student’s prior knowledge. This study was a quasi-experiment with post-test only control group design. The population of the study was 324 ninth grader students of SMPN 3 Denpasar in academic year 2017/2018 where 81 of them were selected as sample through cluster random sampling technique. The data collected in this study was student’s mathematical prior knowledge, which obtained by giving objective tests before starting the learning process and data of student’s mathematical conceptual understanding which obtained by giving an essay test at the end of learning process. The hypotheses were tested using t-test and one-way analysis of covariance test. The results showed that: (1) the usage of GeoGebra-assisted 5E Learning Cycle Model has a positive impact toward student’s understanding of mathematical concept, where t = 2,977 and p = 0,002, (2) the usage of GeoGebra-assisted 5E Learning Cycle Model has a positive impact toward student’s understanding of mathematical concept after the prior knowledge variable was controlled, where F = 31,880 and p = 0,000.Keywords: 5E Learning Cycle, GeoGebra, conceptual understanding, prior knowledge